Pengaruh Penambahan Tepung Bonggol Pisang Kepok (Musa Balbisiana) Terhadap Karakteristik Fisik dan Organoleptik Bakso Daging Rusa (Cervus Timorensis) - Silva Asriani Al Mahdaly; A. Tenny Damayanti Indriastuti; Irine Ike Pratiwi (AGRICOLA, 2019)
This study aims to determine the physical characteristics and organoleptic values ​​of deer meatballs mixed with kapok banana weevil flour (KBWF). The method study used an experimental method using a Completely Randomized Design (CRD) consisting of 5 treatments 3 replications, namely A0 = 100% tapioca flour (TF), A1 = 25% KBWF + 75% TF, A2 = 50% KBWF + 50% TF, A3 = 50% 75 KBWF + 25% TF, A4 = 100% KBWF. Parameters observed included tests of physical characteristics (analysis of water content, cooking losses of water and pH) and organoleptic tests (color, aroma, taste, elasticity, texture). The results of the physical characteristics testing of deer meatball cooking shrinkage with the addition of KBWF had no significant effect and cooking losses were still within the normal threshold (1.55-2.22). The water content of deer meatballs added with KBWF had no significant effect and was still at the level in accordance with SNI meatballs (53.37% -66.67%). The pH value added by KBWF has no significant effect and is still within the permissible pH level (5.50-5.83). Organoleptic test results showed that the addition of TBP had a very significant effect (P <0.01) on color, aroma, suppleness and texture.